Piano Works of Ukrainian Classical and Contemporary Composers as a Means of Formation of Nationally Defined Type of Future Music Teacher Personality - Danilishyna, Margaryta (Pedagogical Discourse, 2013)
The article examines selected piano works related to Ukrainian folk song material and occupy a leading position in the artistic heritage of representatives of the Ukrainian national composers’ school of the XIX-XX centuries. National educational value of piano pieces of different shapes (based on folklore) and their didactic value due to their use in modern educational repertoire for student-musicians of faculties of arts in pedagogical universities are emphasized, since a thorough study of such works in the learning process of playing the piano promote the development of professional skills and abilities, as well as the formation of nationally defined type of future music teacher personality.